Small patella syndrome: New clinical and molecular insights into a consistent phenotype. Issue 6 (9th November 2017) - Vanlerberghe, C.; Jourdain, A.‐S.; Dieux, A.; Toutain, A.; Callewaert, B.; Dupuis‐Girod, S.; Unger, S.; Wright, M.; Isidor, B.; Ghoumid, J.; Petit, F.; Boutry, N.; et al.
Abstract :